Amplified spontaneous emission from PicoGreen dye intercalated in deoxyribonucleic acid lipid complex. (29th October 2015) - Pradeep, C; Vallabhan, C P G; Radhakrishnan, P; Nampoori, V P N
Abstract: DNA as a genetic biomolecule is more commonly referred to in life sciences, genetics, and microbiology. With the development of 'DNA photonics', it has shown tremendous applicability as an optical and photonic material. In this letter, we introduce a novel dye PicoGreen as a lasing medium in which DNA not only acts as a host matrix but also functions as a fluorescence enhancer. A dramatic increase in the fluorescence led us to the observation of optical amplification in dye doped DNA thin films. We also indicate the possible tunability of the output emission in the green–yellow region. With the obtained results, we have enough reasons to lead to the development of DNA-based bio-lasers.